Study of maternal and perinatal outcome in abruptio placentae - Patel, Krupa; Bhatu, Jaydeep; Patel, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abruptio placentae is very frequently seen in our population. Few studies have reported maternal and fetal morbidity and mortality associated with this condition. No work has been done on abruptio placentae in our setup. The data generated will help to improve maternal and fetal morbidity and mortality by planning prompt management of future cases of placental abruption. Objective of this study was to study possible etiological factors of abruptio placentae, analyse maternal outcome, perinatal outcome in the form of maternal morbidity and mortality and discuss possible preventive measures and future management option Methods: The retrospective observational study it was included all cases presenting with ante partum haemorrhage during the study period. Subjects selected for the study were all cases diagnosed as having abruptio placentae. All other causes of APH like placenta previa and other extraplacental causes were excluded. Results: In the present study incidence of abruptio placentae is higher in 25-30 year that were 42.5% and more in 2nd gravida patient. PIH was accounting for 50%, most of the patients (95%) were anaemic at admission and majority of them required blood transfusion.one maternal mortality (2.5%) occurred, perinatal mortality was 75%. Conclusions: Abruptio placentae serious condition with manifestation of significant maternal and perinatal morbidity and mortality. Complications can be reduced by provisional antenatal care to every woman and with improvement in medical facilities, availability of blood transfusion, proper management of shock. With liberalization of caesarean section, the rate of maternal morbidity and mortality is gradually on the decline.